(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Globally diabetes mellitus (T2DM) is a burning issue. Prediction of global estimation that the proportion of diabetes with adult will increase 69% for the year 2030. Hans Selye, the Canadian physiologist, was the first scientist to study the effects of psychological stress on the human body in 1936.Diabetic patients are in a state of high oxidative stress which leading to impaired glucose homeostasis, insulin insufficiency, and other complications.: A randomized controlled trial was conducted to see the effect of the vitamin D supplementation on oxidative stress in vitamin D deficientT2DM patients. In this study, a total of 124 T2DM patients were randomly enrolled, among them Treatment group 61 and placebo 63. In treatment group received 20,000IU vitamin D every 5thDay for three months in addition to regular treatment. Analysis of fasting plasma glucose (FPG), Vitamin D 25(OH)2, malondialdehyde (MDA) and superoxide dismutase (SOD) have been estimated both at the time of study recruitment, at 6th weeks and after 12-weeks of vitamin D supplementation (endline). Present study showed after vitamin D supplementation, baseline mean FBG gradually significantly (P<0.001) decreased at the end line in treatment group as compared to placebo. All biochemical indices by P- trend like FBG, vitamin D, MDA and SOD were significantly different (P<0.05). Whenever, consider between groups vitamin D increased (P<0.05) and FBG decreased significantly (P<0.05) in treatment group as compared to placebo. However, no significant impact on socio-demography variables, vitamin D and Stress-related characteristics between treatment and control groups after vitamin D supplementation as those variables are somewhat independent (p>0.05) both at baseline and end line. The results were considered significant at P<0.05. The statistical calculations were done using SPSS version 26 software. A strong positive co-relation between diabetes and oxidative stress were observed in this study and showed beneficial impact of vitamin D supplementation to reduce oxidative stress those who were vitamin D deficient.